The quality of landing in the gymnastic exercises, as seen by coaches in acrobatic gymnastics and tumbling - Grad, Rafał; Kochanowicz, Kazimierz (Journal of Education, Health and Sport, 2017)
Summary Introduction Landing in gymnastics is an important constituent of the final score and the place of the athlete in competitions. The problem of numerous mistakes made in the course of the landing is noticeable in gymnastics, but disregarded in sport acrobatics. Therefore the aim of this research has been to learn the opinions of Polish coaches of acrobatic gymnastics on landings and the mistakes commonly made in their course. Source material and methods. The research was based on the diagnostic survey, utilizing the questionnaire method. The sample was 22 coaches of acrobatic gymnastics and tumbling, who have been approached during the Championship of Poland of Younger Juniors 2015. Results. The research showed the athletes to commit similar mistakes in landing during competition to those committed during training. This is also significantly affected by previous mistakes, named by the coaches as improper joining of elements and incorrect commencement of the last element. Through exercise routines and games the coaches attempt to eliminate landing mistakes. Conclusions. The most common mistakes both during competitions and in training are steps/skips and unstable positioning of the body. Propping oneself up is significantly more common during competitions than it is during training, since it reduces the loss of points compared to the athlete falling down. During training, however, the athletes do not avoid falls, which results in smaller frequency of injuries during training. According to the coaches, the most important coordination capabilities for correct landing are: spatial orientation, balance and fast reaction time.